Artificial Diploid Escherichia coli by a CRISPR Chromosome‐Doubling Technique. Issue 7 (15th January 2023) - Wang, Pengju; Zhao, Dongdong; Li, Ju; Su, Junchang; Zhang, Chunzhi; Li, Siwei; Fan, Feiyu; Dai, Zhubo; Liao, Xiaoping; Mao, Zhitao; Bi, Changhao; Zhang, Xueli
Abstract: Synthetic biology has been represented by the creation of artificial life forms at the genomic scale. In this work, a CRISPR‐based chromosome‐doubling technique is designed to first construct an artificial diploid Escherichia coli cell. The stable single‐cell diploid E. coli is isolated by both maximal dilution plating and flow cytometry, and confirmed with quantitative PCR, fluorescent in situ hybridization, and third‐generation genome sequencing. The diploid E. coli has a greatly reduced growth rate and elongated cells at 4–5 µm. It is robust against radiation, and the survival rate after exposure to UV increased 40‐fold relative to WT. As a novel life form, the artificial diploid E. coli is an ideal substrate for research fundamental questions in life science concerning polyploidy. And this technique may be applied to other bacteria. Abstract : An artificial diploid Escherichia coli cell constructed by a CRISPR‐based chromosome‐doubling technique has a greatly reduced growth rate and elongated cell. As a novel life form, the diploid E. coli is robust against radiation and an ideal substrate for researching fundamental questions in life science concerning polyploidy. And this technique might be applied to other bacteria.